Characteristics of the images of Chinese politicians in the national media - Ilgam F. Fattakhov, Ramis R. Gazizov, (Opción, 2019)
This study is devoted to the definition of media images specifics for national politicians from the Republic of China’s people in Chinese mass media via system analysis, content analysis, and comparative analysis methods. As a result, the central figures are governors and other regional officials, party leaders, what justifies the status of provincial publications and confirms their dependence on the authorities. As conclusion, the images of Chinese politicians as the fathers of the nation are ideological in nature; they are intended to unite the nation in front of world threats and challenges.